ENHANCEMENT OF OIL PALM FRONDS GASIFICATION PROCESS USING PREHEATED INLET AIR - MEKONNEN GUANGUL, FISEHA (2013)
Emissions of greenhouse gases from fossil fuels and an ever growing demand for energy source which is in dissonance with a limited supply of fossil fuels are the current pressing global problems which need sustainable solution. Malaysia has abundant but underutilized oil palm fronds (OPF) which could be used as a source of renewable energy through appropriate conversion technologies. Conversion of biomass into producer gas through gasification process is one of the promising technologies to alleviate the aforementioned problems. Recently, gasification of biomass using preheated air has been found as an efficient and environmentally friendly method. However, the research works done with this method are few and restricted to certain types of biomass wastes and gasifier designs.